Synergistic effects of retinol and retinyl palmitate in alleviating UVB-induced DNA damage and promoting the homologous recombination repair in keratinocytes - Zhong, Jiangming; Liang, Ling; Zhao, Nan; Wang, Jing; Shu, Peng (Frontiers in Pharmacology, 2025)
BackgroundUltraviolet B (UVB) rays are a type of ultraviolet radiation emitted by the sun, primarily responsible for skin photodamage. These rays mainly affect the epidermis, leading to direct damage to DNA and contributing to skin cancer development. Retinol and its derivatives are effective in combating skin aging and photodamage, but they often cause skin intolerance, limiting their use despite their potent effects. Therefore, investigating optimal compositions of retinoids is essential to enhance their efficacy against photodamage.MethodIn this study, we investigated the synergistic effects of retinol (ROL) and retinyl palmitate (RPalm) in alleviating UVB-induced DNA damage in human keratinocytes (HaCaT) and reconstructed human epidermis. The ROL+RPalm combination was applied after UVB exposure. We utilized bulk mRNA sequencing, comet assays, Western blotting, immunofluorescence, and flow cytometry to evaluate the level of DNA damage and repair.ResultThe application of the ROL+RPalm combination significantly reduced inflammation and apoptosis while promoting collagen synthesis compared to individual treatments with ROL or RPalm. Our findings indicated that the ROL+RPalm synergy primarily mediates DNA damage repair. Additionally, we elucidated that the molecular mechanism involves the activation of RARβ, which triggers the ATM-CHK2-p53 signaling pathway and increases the expression of homologous recombination (HR)-associated repair genes.ConclusionThis combination of ROL and RPalm presents a potential therapeutic strategy for UVB-induced photodamage and emphasizes the synergistic effects in alleviating UVB-induced DNA damage.